Online learning experiences among the post-graduate learners during the COVID-19 pandemic in a higher medical educational institution in Bangladesh (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
The COVID-19 pandemic had substantial effects on education. As a result, online education has gained popularity among postgraduate medical students. The aim of this study was to explore postgraduate learners’ experiences regarding online classes. This study was carried out in the Department of Neonatology, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh, from March 2020 to September 2020. A questionnaire was sent to neonatology and pediatrics allied residents and students of FCPS paediatrics. Qualitative data were collected and using likert scales to assess satisfaction regarding online learning experience. The study included 79 participants. Of them, 71 (89.9%) responded, 12 (16.9%) attended online classes before the COVID-19 situation. Thirty-four (47.9%) residents opined that online classes provided the right amount of theory. Eighteen (25.4%) disagreed that high-quality learning can be accomplished without face-to-face contact. Twenty-four respondents (33.8%) disagreed that studying online was more motivating than attending a regular classes. Fortytwo (59.2%) concluded that online class was really beneficial, and 50 (70.4%) were satisfied with online education. More than half of them (57.7%) preferred online theoretical classes compelling situation. Though students prefer online education as an alternative to classroom education, both face-to -face and online teachings are necessary.BSMMU J 2022; 15(3): 151-156